A Minireview of Microfluidic Scaffold Materials in Tissue Engineering - Tong, Anh; Voronov, Roman (Frontiers in Molecular Biosciences, 2022)
In 2020, nearly 107,000 people in the U.S needed a lifesaving organ transplant, but due to a limited number of donors, only ∼35% of them have actually received it. Thus, successful bio-manufacturing of artificial tissues and organs is central to satisfying the ever-growing demand for transplants. However, despite decades of tremendous investments in regenerative medicine research and development conventional scaffold technologies have failed to yield viable tissues and organs. Luckily, microfluidic scaffolds hold the promise of overcoming the major challenges associated with generating complex 3D cultures: 1) cell death due to poor metabolite distribution/clearing of waste in thick cultures; 2) sacrificial analysis due to inability to sample the culture non-invasively; 3) product variability due to lack of control over the cell action post-seeding, and 4) adoption barriers associated with having to learn a different culturing protocol for each new product. Namely, their active pore networks provide the ability to perform automated fluid and cell manipulations (e.g., seeding, feeding, probing, clearing waste, delivering drugs, etc.) at targeted locations in-situ. However, challenges remain in developing a biomaterial that would have the appropriate characteristics for such scaffolds. Specifically, it should ideally be: 1) biocompatible—to support cell attachment and growth, 2) biodegradable—to give way to newly formed tissue, 3) flexible—to create microfluidic valves, 4) photo-crosslinkable—to manufacture using light-based 3D printing and 5) transparent—for optical microscopy validation. To that end, this minireview summarizes the latest progress of the biomaterial design, and of the corresponding fabrication method development, for making the microfluidic scaffolds.